The Political Economy of Collective Bargaining - Tapio Palokangas (Center for Economic Studies and ifo Institute (CESifo), 2002)
We construct a political equilibrium in which employers and labour unions bargain over labour contracts, wage-earners and profit-earners lobby the government for taxation and labour market regulation, and labour market legislation must be accepted by the majority of voters. We show that the voters rule out profit sharing, because otherwise the government would capture all the gain. Furthermore, if it is much easier to tax wages than profits, then the government protects union power by regulation in the labour market. In such a case, the political equilibrium is characterized by strong union power and right-to-manage bargaining, which causes involuntary unemployment.
Keywords: 330; regulation; lobbying; collective bargaining